2016
DOI: 10.2519/jospt.2016.0606
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Prediction Rules That Don't Hold Up—Where to Go From Here?

Abstract: Clinical prediction rules (CPRs) are created to help guide clinical decision making. To do this, they use the presence or absence of certain factors that have been shown to meaningfully predict a patient's prognosis, diagnosis, or response to treatment. While representing a seminal methodological step forward in individualized care, one of the main drawbacks of CPRs continues to be validation studies that do not support the initially derived CPR. This is particularly important because validation of CPRs in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The clinical prediction rule (or predictive model, probability assessment, decision rule, risk score) [36] is a decision-making tool for clinicians with three or more variables obtained from the history, physical examination, and simple diagnostic tests. They are derived from the data collected directly from patients [36][37][38]. They provide powerful tools to improve clinical decision making [39].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical prediction rule (or predictive model, probability assessment, decision rule, risk score) [36] is a decision-making tool for clinicians with three or more variables obtained from the history, physical examination, and simple diagnostic tests. They are derived from the data collected directly from patients [36][37][38]. They provide powerful tools to improve clinical decision making [39].…”
Section: Introductionmentioning
confidence: 99%
“…as treatment effect modifiers) is unwarranted. Second, there are known limitations in the generalizability of CPRs in that devised models are often taken from homogenous samples and not often validated in subsequent samples (Stanton, 2016). However, given that our data came from orthopaedic surgery departments in 14 different institutions, we believe that our model is based on a well-represented, diverse sample.…”
mentioning
confidence: 99%
“…Even though multiple systematic reviews have raised concerns about the value of these prediction rules and the validation of these tools [ 19 , 88 ], similarly to Puentedura et al, we found that being aware of spine CPRs impacted the beliefs on safety, the perception of effectiveness, and the utilization of SM [ 28 ]. Notably, the fact remains that none of the prescriptive CPRs in physiotherapy are recommended for application in clinical practice as validation and impact analysis studies are still lacking [ 89 ].…”
Section: Discussionmentioning
confidence: 99%